Sistem Evaluasi Cara Pergudangan dan Distribusi yang Baik untuk Menjamin Mutu dan Keamanan Susu Bubuk - I P G Arya Dharmawan; Harsi Dewantari Kusumaningrum; Winiati Pudji Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Good practices in food chain are very important to ensure product quality and safety. Good practices start from raw material usage, manufacturing, warehousing, distribution, retailing, until product consumption by consumers. Milk powder is a high value commodity but it is a high risk product. Good warehousing and distribution system must be in place to ensure product quality and safety. Quality and food safety system evaluation model consists of 4 steps: plan, do, check, and action. A model on quantitative evaluation system for good warehouse practice (GWP) and good distribution practice (GDP) consist of five points (internal, external area, transportation, quality management, and inventory management). These five points were detailed to 30 sub points. Criteria and requirements have been included for each sub point, and defined by 5 scales (0, 1, 2, 3, and 4). Furthermore, the evaluation system has been implemented at 3 distributors (A, B, and C) in 30 cities. The result showed that distri- butors A, B and C complied to the criteria with the score of 77.32+4.05%, 84.17+5.80%, and 73.30+ 6.64%, respectively. The distributors were categorized as very good (13.30%), good (60.0%) and fair (13.30%).